Microstructure evolution and mechanical properties of high Nb–TiAl alloy/GH4169 joints brazed using CuTiZrNi amorphous filler alloy. (December 2021) - Dong, Duo; Shi, Kangqiao; Zhu, Dongdong; Liang, Yongfeng; Wang, Xiaohong; Wei, Zunjie; Lin, Junpin
Abstract: A CuTiZrNi amorphous filler metal was fabricated and utilized for brazing high Nb–TiAl alloys and GH4169 superalloys. The microstructure and mechanical properties of the high Nb–TiAl/GH4169 joints brazed from 900 °C to 1020 °C temperature range were studied. Results showed that the high Nb–TiAl/GH4169 joints consisted of three zones. The interfacial microstructure of the joints was high Nb–TiAl alloy/Ti3 Al + Al3 (Ni, Cu)Ti2 + Al(Ni, Cu)2 Ti/AlCu2 (Ti, Zr) + (Ti, Zr)(Ni, Cu) + Ti2 (Ni, Cu)/Cr-rich (Cr, Ni, Fe)ss + Ni-rich (Ni, Cr, Fe)ss/GH4169 alloy. The element diffusion between the substrates and the filler alloy was intensified as the brazing temperature increased, and the interfacial reaction layer thickened. At 960 °C, the joint exhibited a maximum shear strength which was approximately 241.9 MPa. At higher brazing temperatures, the excessive AlCu2 (Ti, Zr) phase and coarse Ti2 (Ni, Cu) deteriorated the joint properties due to their inherent brittleness. Highlights: CuTiZrNi amorphous filler was used to braze the high Nb–TiAl alloys and GH4169 superalloys. The formation mechanism and microstructure evolution of the joints were studied. Excessive AlCu2 (Ti, Zr) phase and coarse Ti2 (Ni, Cu) phase deteriorated the mechanical properties of the joint. Maximum shear strength of the joint is approximately 241.9 MPa.